B.06 Whole exome sequencing in genetic ataxias associated with cerebellar atrophy: the Canadian experience. (June 2019) - Gauquelin, L; Hartley, T; Tarnopolsky, M; Dyment, DA; Brais, B; Geraghty, MT; Tétreault, M; Ahmed, S; Rojas, S; ,; ,; Majewski, J; et al.
Abstract : Background: Cerebellar atrophy is characterized by loss of cerebellar tissue, with evidence on brain imaging of enlarged interfolial spaces compared to the foliae. Genetic ataxias associated with cerebellar atrophy are a heterogeneous group of disorders. We investigated the prevalence in Canada and the diagnostic yield of whole exome sequencing (WES) for this group of conditions. Methods: Between 2011 and 2017, WES was performed in 91 participants with cerebellar atrophy as part of one of two national research programs, Finding of Rare Genetic Disease Genes (FORGE) or Enhanced Care for Rare Genetic Diseases in Canada (Care4Rare). Results: A genetic diagnosis was established in 58% of cases (53/91). Pathogenic variants were found in 24 known genes, providing a diagnosis for 46/53 participants (87%), and in four novel genes, accounting for 7/53 cases (13%). 38/91 cases (42%) remained unsolved. The most common diagnoses were channelopathies in 12/53 patients (23%) and mitochondrial disorders in 9/53 (17%). Inheritance was autosomal recessive in the majority of cases. Additional clinical findings provided useful clues to some of the diagnoses. Conclusions: This is the first report on the prevalence of genetic ataxias associated with cerebellar atrophy in Canada, and the utility of WES for this group of conditions.